Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Belanja Modal di Kota Jambi - M Zahari MS (Universitas Batanghari Jambi, 2018)
This study aims to analyze: (1) Effect of Regional Tax and Local Retribution on Capital Expenditure in Jambi City. (2), Effect of Regional Tax on Capital Expenditure in Jambi City. (3) Effect of Regional Retribution on Capital Expenditure in Jambi City.The object of research was conducted in Jambi City, with observation during the period 2003 - 2017. Data analysis used multiple linear regression, with data processing tool through SPSS 20 software. The result of the research shows that: (1) Regional Tax and Regional Retribution have significant effect to Capital Expenditure, it means that the increasing of Regional Tax and Regional Retribution will increase the allocation of capital expenditure. (2) Regional Tax has significant effect to capital expenditure, meaning that with increasing of local tax revenue, it will increase capital expenditure (3) Levy does not have significant effect to capital expenditure, it means that the increase of local retribution revenue has not been able to increase the allocation of capital expenditure.